Environmental information disclosure and stock price crash risk: Evidence from China - Ge, Yongbo; Chen, Qi; Qiu, Shiwen; Kong, Xiaoran (Frontiers in Environmental Science, 2023)
Using the sample of Chinese A-share listed firms from 2013 to 2018, this paper empirically tests the relationship between environmental information disclosure and the risk of stock price crash. The results show that environmental information disclosure has a significant negative correlation with stock price crash risk. Mechanism analysis showed that the media coverage plays an intermediary role between them. Further analysis shows that the inhibitory effect of environmental information disclosure on stock price crash is more obvious in companies with lower proportion of independent directors, which reflects the supervision effect of environmental information disclosure; The role of environmental information disclosure has a more significant negative impact on the risk of stock price crash in industries with low competition, indicating that environmental information disclosure is not a tool for enterprises to compete for resources; The profit motivation of institutional investors restrains the negative impact of environmental information disclosure on price collapse risk; The level of government environmental governance is an important support for enterprise environmental information disclosure. The research of this paper reveals the effect and mechanism of non-financial information disclosure on improving the market information environment, which has a good reference significance for perfecting the information disclosure system, strengthening the government's environmental governance, and preventing systemic financial risks.